The Impact of Establishment King Abdullah University for Science and Technology on the Urban Growth in Thuwal Center in Jeddah Governorate - Bakhsh, Aisha Abdulkareem Ataallah (Journal of Humanities & Social Sciences, 2023)
This study aims to identify the stages of urban growth and its trends in the Thuwal Center between 1985-2021 AD and to know the extent of the impact of the establishment of King Abdullah University of Science and Technology on urban growth during the period 2007 AD-2021 AD The research relied on the analytical descriptive approach to reveal the extent to which urban growth was affected by the establishment of King Abdullah University of Science and Technology, by using land sat 5.7 and SPOT 6 satellite visuals and analyzing them using the ARC MAP10,8 program. The results of the study found that the establishment of King Abdullah University of Science and Technology in the Thuwal Center had a clear effect with regard to increasing the area of the urban mass, as the urban growth was slow before the establishment of the university and doubled after the establishment of the university 7 times more than it was before, as it was in the year 2007 AD approximately 3.39 km2 reached 23.04 km2 in 2010. The study also concluded that the establishment of the university did not have a clear effect in attracting the urban mass around its perimeter and direction, as a result of the presence of residential facilities, in addition to the fact that it includes various services that it provides to students, faculty and staff, which led to weak interaction between it and the Thuwal Center. The study recommended an improvement in the quality of life in the Thuwal Center by utilizing and investing in vacant lands, improving the urban landscape, and removing and developing the slums near King Abdullah University of Science and Technology.